Features of the computer modeling of loading of container with elastic-related connections in the fittings in operating modes (Transport systems and technologies, 2019)
The article presents the results of computer simulation of the dynamic loading of the container of the improved design, located on the platform carriage, with maneuvering coaxing. The design feature of the container is the presence in the fittings of viscous and elastic-viscous bonds, which allows ensuring the dynamic loading of the container within the limits of the normative.The mathematical modeling of the dynamic loading of the container is carried out taking into account the elastic, viscous and elastic-viscous bonds between the fittings and the fittings of the platform carriage. It has been established that the elastic bond does not compensate for the dynamic loads that act on the container placed on the platform carriage while maneuvering the bending. When viscous and elastic-viscous interaction of fittings with fittings, the value of dynamic loads is within the permissible limits.The results of computer modeling of the dynamic loading of the container are presented. The calculation is based on the finite element method implemented in the CosmosWorks software environment. The magnitudes and fields of concentration of accelerations acting on the container are determined. Verification of the developed models is carried out according to the F-criterion.The results of the research will promote the creation of new generation containers with improved performance and increase the efficiency of container transport operations.
Keywords: контейнер, моделирование, динамическая нагруженность, ускорения, контейнерные перевозки